Evaluation of Mechanical Properties of Asphaltite and SBS Modified Hot Mix Asphalts - Kok, Baha Vural; Yilmaz, Mehmet; Kuloglu, Necati (Gazi Univ, 2011)
In this study the styrene-butadiene-styrene (SBS) of which usage is became prevalent in bitumen modification and asphaltite which is a petrol origin material were used as an additive material in order to improve the performance of hot mix asphalt. Asphaltite was added into mix as 50% by weight of filler, SBS was added to bituminous binder as 5% by weight. The used pure binder in the mixtures is B160/220 and aggregate is calcareous orgined. The specimens were prepared according to Marshall procedure. Hot mix asphalt specimens were produced in 4 different combinations including additive materials and control specimens. The effects of using additive materials separately and using together were evaluated by means of these combinations. The indirect tensile stiffness modulus, indirect tensile strength and fatigue tests were applied on prepared specimens. In conclusion it was determined that the engineering properties of modified mixtures were improved significantly compared to control mixtures. This improvement effect changed between the experiments. Especially the fatigue test was determined as the most active test method to identify the effects of additive material. It was also determined that the mixtures in which SBS and asphaltite used together exhibited high performance. Leads to air pollution when used as a heating material, asphaltite provides to construct more stable and requires less maintenance roads by improving the mechanical properties of hot mix asphalt. The usage of asphaltite in this way will ensure ecological sustainability by facilitating the prevention of ecosystem, and also will ensure economical sustainability by reducing the operation cost of roads in long term.
Keywords: Hot mix asphalt; asphaltite; SBS